Transportation Barriers to Successful Reentry among Returning Citizens: A Qualitative Interpretive Meta-synthesis. (September 2021) - Nordberg, Anne; Davis, Jaya B.; Leat, Sara R.; Mattingly, Stephen; Keaton, Craig; Mitchell, Michael B.
Over 600, 000 individuals return to United States communities from prison each year. Transportation has been identified as a major barrier to successful reentry. Applying qualitative interpretive meta-synthesis to achieve a deep understanding of reentry transportation obstacles, 11 articles with 362 male and female participants were identified. Two themes emerged from our analysis: (1) "Transportation connects complex obligations, " highlighting the critical role that transportation plays in the successful navigation of post-release conditions; and (2) "Transportation deficiencies exacerbate vulnerability, " revealing how transportation factors intertwine with structural issues to increase precarity.